Late gastric twist after laparoscopic sleeve gastrectomy - Lopez, Elsa Paulina Alonso; Sahagun, Cesar Manuel Vargas; Ortiz, Cesar Antonio Martinez (International Journal of Research in Medical Sciences, 2022)
Gastric sleeve twist is a rare complication, with an incidence of 1.2%. Its symptomatology is not very specific, making its diagnosis difficult to establish. Its timely treatment by endoscopy and/or surgery has shown excellent short- and long-term results. We present an infrequent and rare case of late gastric torsion 10 years after a laparoscopic gastric sleeve, which was resolved with surgical treatment with conversion to Laparoscopic Roux-en-Y Gastric Bypass with excellent results.